Indwelling pleural catheter for outpatient management of tuberculous empyema. Issue 3 (8th March 2020) - Iqbal Muhammad, Ambreen; Gavin, Joseph; Wilkinson, Alex
Abstract : The use of indwelling pleural catheters (IPC) is well established in the treatment of malignant pleural effusions. They allow symptom management with intermittent drainage without requiring overnight admission to hospital. However, little is known about their effectiveness in the treatment of pleural infections. Here, we present a case where an IPC is used in the therapeutic management of tuberculous empyema. The IPC enabled outpatient treatment, allowed the patient to return to work and reduced the cost of treatment and the risk of hospital-acquired complications.